Effect of the Addition of Cu and Al on the Microstructure, Phase Composition and Properties of a Ti-6Al-4V Alloy Obtained by Selective Laser Melting - Galina M. Zeer; Yuri I. Gordeev; Elena G. Zelenkova; Artur K. Abkaryan; Evgeny V. Gerasimov; Mikhail Yu. Kuchinskii; Sergey M. Zharkov (Metals)
The present study considers the samples of an Ti-6Al-4V alloy obtained by selective laser melting with the addition of a 10% Cu-Al powder mixture. The microstructure, elemental composition and phase composition, as well as the physico-chemical properties, have been investigated by the methods of electron microscopy, X-ray phase analysis, and bending testing. The obtained samples have a relative density of 98.5 ± 0.1%. The addition of the Cu-Al powder mixture facilitates supercooling during crystallization and solidification, which allows decreasing the size and changing the shape of the initial β-Ti grains. The constant cooling rate of the alloy typical for the SLM technology has been shown to be able to prevent martensitic transformation. The formation of a structure that consists of β-Ti grains, a dispersed eutectoid mixture of α-Ti and Ti2Cu grains, and a solid solution of Al in Cu has been revealed. In the case of doping by the 10% Cu-Al mixture, the physico-mechanical properties are improved. The hardness of the samples amounts to 390 HRC, with the bending strength being 1550 ± 20 MPa and deformation of 3.5 ± 0.2%. The developed alloy can be recommended for applications in the production of parts of jet and car engines, implants for medicine, and corrosion-resistant parts for the chemical industry.